Accurate cancer cell identification and microRNA silencing induced therapy using tailored DNA tetrahedron nanostructures. Issue 1 (8th November 2019) - Su, Juan; Wu, Fubing; Xia, Hongping; Wu, Yafeng; Liu, Songqin
Abstract : DNA tetrahedron nanostructures (DTNSs) were prepared to improve the accuracy of cancer diagnosis through real-time monitoring and imaging three intracellular miRNAs, as well as to realize cancer therapy induced by miRNA silencing. Abstract : Accurate cancer cell identification and efficient therapy are extremely desirable and challenging in clinics. Here, we reported the first example of DNA tetrahedron nanostructures (DTNSs) to real-time monitor and image three intracellular miRNAs based on the fluorescence "OFF" to "ON" mode, as well as to realize cancer therapy induced by miRNA silencing. DTNSs were self-assembled by seven customized single-stranded nucleic acid chains containing three recognition sequences for target miRNAs. In the three vertexes of DTNSs, fluorophores and quenchers were brought into close proximity, inducing fluorescence quenching. In the presence of target miRNAs, fluorophores and quenchers would be separated, resulting in fluorescence recovery. Owing to the unique tetrahedron-like spatial structure, DTNSs displayed improved resistance to enzymatic digestion and high cellular uptake efficiency, and exhibited the ability to simultaneously monitor three intracellular miRNAs. DTNSs not only effectively distinguished tumor cells from normal cells, but also identified cancer cell subtypes, which avoided false-positive signals and significantly improved the accuracy of cancer diagnosis. Moreover, the DTNSs could also act as an anti-cancer drug; antagomir-21 (one recognition sequence) was detached from DTNSs to silence endogenous miRNA-21 inside cells, which would suppress cancer cell migration and invasion, and finally induce cancer cell apoptosis; the result was demonstrated by experiments in vitro and in vivo . It is anticipated that the development of smart nanoplatforms will open a door for cancer diagnosis and treatment in clinical systems.